2022
DOI: 10.5603/rpor.a2022.0012
|View full text |Cite
|
Sign up to set email alerts
|

Tomotherapy-based moderate hypofractionation for localized prostate cancer: a mono-institutional analysis

Abstract: This article is available in open access under creative common attribution-Non-commercial-No Derivatives 4.0 International (cc BY-Nc-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Tenti et al recently retrospectively analyzed 76 patients treated with a total dose of 60 Gy in 20 fractions or 67.5 Gy in 25 fractions for localized PCa. After a median follow-up of 42.46 months, they obtained a 4y OS and MFS of 91% and 89%, respectively, with acute and late G ≥2 GI toxicity reported in 6.5% and 2.6% of patients, respectively, and acute and late G ≥2 GU toxicity in 31.5% and 3.9% (33). The authors also reported an interesting association between acute GI toxicity and statin medication and ADT, the latter not found in our analysis, and a relation of acute GU toxicity and use of anticoagulants and antiaggregants.…”
Section: Discussionmentioning
confidence: 99%
“…Tenti et al recently retrospectively analyzed 76 patients treated with a total dose of 60 Gy in 20 fractions or 67.5 Gy in 25 fractions for localized PCa. After a median follow-up of 42.46 months, they obtained a 4y OS and MFS of 91% and 89%, respectively, with acute and late G ≥2 GI toxicity reported in 6.5% and 2.6% of patients, respectively, and acute and late G ≥2 GU toxicity in 31.5% and 3.9% (33). The authors also reported an interesting association between acute GI toxicity and statin medication and ADT, the latter not found in our analysis, and a relation of acute GU toxicity and use of anticoagulants and antiaggregants.…”
Section: Discussionmentioning
confidence: 99%